Effect of calcium salts and surfactant concentration on the stability of water-in-oil (w/o) emulsions prepared with polyglycerol polyricinoleate - Márquez, Andrés Leonardo (2010)
The objective of this work was to obtain water-in-oil (w/o) emulsions with polyglycerol polyricinoleate (PGPR) as emulsifier and to study the effect of the addition of calcium in the dispersed aqueous phase on the stability of these systems. Emulsions were formulated with 0.2, 0.5 and 1.0% w/w PGPR and 10% w/w water containing calcium chloride at varied concentrations or other salts (calcium lactate or carbonate; sodium, magnesium or potassium chloride). The stability of these systems was studied with a vertical scan analyzer during 15 days; coalescence and sedimentation were observed as simultaneous destabilization processes. The increase of PGPR concentration and/or calcium chloride content gave more stable emulsions. The stabilizing effect of calcium salt was attributed to the diminution of the water droplets size, the decrease of the attractive force between water droplets and the increase of the adsorption density of the emulsifier. The viscoelastic parameters of the interfacial film were decreased with increasing calcium and PGPR concentrations. Calcium chloride produced a higher increase of stability than calcium salts with lower dissociation degree. The presence of any assayed salt in the aqueous phase also allowed the stabilization of w/o emulsions with higher water contents. © 2009 Elsevier Inc. All rights reserved.